Persepsi Hunian Subsidi Berdasarkan Penghuni di Kota Makassar - Amelia, Nonny Rifka Rizky; Hayati, Arina; Faqih, Muhammad (Arsir, 2023)
Limited land area and increasing population have made housing prices in big cities expensive, so the provision of subsidized housing has also expanded. The problem that often occurs in subsidized housing is the design of housing that does not take into account the needs of the occupants. Subsidized houses that are not in accordance with the wishes can affect the occupants' perception of comfort towards the available subsidized houses. This study aims to determine the perceptions of residents in Makassar City on the available subsidized housing depending on the desired needs. The research method used is quantitative using a questionnaire to determine the comfort perception of the architectural elements of subsidized houses by questioning several aspects that can be seen from the characteristics of the occupants and then analyzed using a Likert scale with cross tabulation (SPSS) which is associated with the characteristics of the occupants. The results of research are cross-tabulated occupant perceptions and associated with occupant characteristics indicating that the perceptions and occupant profiles in Makassar City on average feel comfortable with the space available for their activities. But there are also those who are uncomfortable so that they may need to add or expand space and change the function of space to support their daily needs.